Democratization and Extremism: The Case of Tunisia - Abdelaty, Mariam (AUC Knowledge Fountain, 2021)
Terrorism has become a real security threat for nearly every country in the world. Despite of the declaration and adoption of several procedures to fight terrorism and its perpetrators, countries have not yet succeeded to control the huge numbers of recruits being mobilized by terrorist organizations.[1] The literature has covered several factors that make recruits vulnerable and easily mobilized and radicalized by terrorist organizations, among which is the suppression of civil and political rights in non-democratic countries, as well as weak political institutions.[2] Among the Arab world countries, it has been puzzling to find out that despite of being the sole democratizing Arab country, Tunisia has been found to generate the greatest number of foreign fighters joining jihadist groups.[3] At the same time, the country’s main Islamist party, Ennahda, decided to back up the new democratic government after the Arab Spring, accept a constitution that contradicts the party’s Islamist ideology, and be part of the democratization process in Tunisia.[4] Not only that, but also, Ennahda party was able to win the elections of the Constituent Assembly with a momentous margin, as the party won 89 seats out of a total of 217 seats.[5] Therefore, Tunisia has been a battle ground for these two competing mechanisms; the issue which poses an empirical puzzle for this thesis. Hence, the main research question of this thesis would be: why has the democratic transition in Tunisia been associated with a high rate of recruits joining terrorist organizations? [1]Almakan Orozobekova, "The Mobilization and Recruitment of Foreign Fighters: The Case of Islamic State, 2012–2014." Partnership for Peace Consortium of Defense Academies and Security Studies Institutes15, no. 3 (2016): 83-100, p. 83. [2]Geoffrey Macdonald, and Luke Waggoner, "Dashed Hopes and Extremism in Tunisia." Journal of Democracy29, no. 1 (2018): 126-140, p. 126. [3]Meirav Mishali-Ram, "Foreign Fighters and Transnational Jihad in Syria." Studies in Conflict & Terrorism 41, no. 3 (2018): 169-190, p. 170.; Ric Neo, "The Jihad post-Arab Spring: Contextualising Islamic radicalism in Egypt and Tunisia." African Security Review 28, no. 2 (2019): 95-109, p. 100. [4]Fabio Merone, "Between social contention and takfirism: the evolution of the Salafi-jihadi movement in Tunisia." Mediterranean Politics22, no. 1 (2017): 71–90, p. 81.; Geoffrey Macdonald, and Luke Waggoner, "Dashed Hopes and Extremism in Tunisia." Journal of Democracy(Johns Hopkins University Press) 29, no. 1 (2018): 126-140, p. 126. [5]Ahmad Najib Burhani, "The Reformasi ’98 and the Arab Spring: A Comparative Study of Popular Uprisings in Indonesia and Tunisia." Asian Politics & Policy(Wiley Periodicals, Inc.) 6, no. 2 (2014): 199-215, p. 199.